2021
DOI: 10.3390/genes12121863
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Analysis of Primordium Formation in Pleurotus eryngii

Abstract: Primordium formation is an important stage preceding the growth and development of the Pleurotus eryngii fruiting body. However, the molecular mechanisms underlying primordium formation remain unclear. In the present study, comparative transcriptomics was performed between mature mycelia and primordium to analyze the transcriptional properties during primordium formation in P. eryngii. A total of 19,655 differentially expressed genes (10,718 upregulated genes and 8937 downregulated genes) were identified. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Similar to common edible mushrooms, the nutritional and reproductive growth of morels show very different features and dynamics (Figures 1a and 6). Primordium formation is considered to be a critical "intermediate" or "transitional" phase for successful differentiation into ascocarps [58][59][60]. Our results support that primordium formation is triggered by changing comprehensive environmental information (e.g., nutrient availability, temperature, light, humidity, and oxygen) and involves a transition from nutritional mycelia to primordia, which differentiate into reproductive complex structures.…”
Section: Discussionsupporting
confidence: 78%
“…Similar to common edible mushrooms, the nutritional and reproductive growth of morels show very different features and dynamics (Figures 1a and 6). Primordium formation is considered to be a critical "intermediate" or "transitional" phase for successful differentiation into ascocarps [58][59][60]. Our results support that primordium formation is triggered by changing comprehensive environmental information (e.g., nutrient availability, temperature, light, humidity, and oxygen) and involves a transition from nutritional mycelia to primordia, which differentiate into reproductive complex structures.…”
Section: Discussionsupporting
confidence: 78%
“…The growth and development of edible fungi are generally divided into two stages, vegetative growth and reproductive growth, among which the formation of primordium is an important and sensitive stage in the transition from vegetative growth to reproductive growth [ 23 ]. In this stage, those mycelia twisted together to form a mycelial community, forming a mass of undifferentiated protoplasm tissue called the primordium or fruiting body [ 5 ]. In the mushroom-forming basidiomycete Schizophyllum commune , a regulator of G-protein signaling, Thn1, was involved in the development via pheromone signaling that affects physiological interactions [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. eryngii is one of the most valuable edible mushroom species in China and other Asian countries because of its thick flesh, delicious taste, and medicinal value [ 2 ]. Previous studies have demonstrated that P. eryngii exhibited various biological activities, including antioxidant, immunomodulatory, bacteriostatic, and tumor-inhibitory effects [ 3 , 4 , 5 ]. Mushroom development of P. eryngii can be divided into three stages: hyphal knot, primordium, and fruiting body [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent transcriptome analysis is also available for Pleurotus eryngii (kings trumpet), a close relative of P. ostreatus [ 20 ]. A comparison of transcriptomics of mature mycelia and primordia showed a total of 10,718 upregulated and 8937 downregulated genes in the primordium library.…”
Section: From Mycelium To Fruiting Body: Differential Gene Expressionmentioning
confidence: 99%